Information presentation in annual reports: The case of award winning companies in Malaysia 2000-2010 - Ibrahim, Mohammad Azhar; Harun Rasit, Mohd Hadzrami; John Jones, Michael (2013)
The way in which the information is presented in the corporate annual report is important, for it determines the readability and understandability of the report. An appropriate form of information presentation helps to improve the effectiveness of the communication process. Information, if presented in an appropriate form, is able to guide viewers’ interpretation to particular outcomes. This will improve the communication efficiency and also enhance the quality of decision-making.The annual report, in the past few decades, has evolved from a financially -driven document to one used to construct a corporate image, to the extent that financial statements are relegated to a technical “appendix”.The front half of the report is used to influence and manage the way in which the information is presented to readers.This paper examines the presentation formats of photographs, graphs, tables, and text in pages prior to the financial statements section of the National Annual Corporate Report Award (NACRA) best presentation annual reports 2000–2010.The discretionary material is mostly textual, followed by photographic, tabular, and graphical presentation.This study not only adds to the accounting literature on voluntary disclosures involving photographs and graphs in particular, but also potentially benefits those companies competing in the future NACRA competition in improving the way in which the corporate information is communicated.